Mortality among workers at the Los Alamos National Laboratory, 1943–2017. (3rd April 2022) - Boice, John D.; Cohen, Sarah S.; Mumma, Michael T.; Golden, Ashley P.; Howard, Sara C.; Girardi, David J.; Ellis, Elizabeth Dupree; Bellamy, Michael B.; Dauer, Lawrence T.; Samuels, Caleigh; Eckerman, Keith F.; Leggett, Richard W.
Abstract: Background: During World War II (WWII), the Manhattan Engineering District established a secret laboratory in the mountains of northern New Mexico. The mission was to design, construct and test the first atomic weapon, nicknamed 'The Gadget' that was detonated at the TRINITY site in Alamogordo, NM. After WWII, nuclear weapons research continued, and the laboratory became the Los Alamos National Laboratory (LANL). Materials and methods: The mortality experience of 26, 328 workers first employed between 1943 and 1980 at LANL was determined through 2017. Included were 6157 contract workers employed by the ZIA Company. Organ dose estimates for each worker considered all sources of exposure, notably photons, neutrons, tritium, 238 Pu and 239 Pu. Vital status determination included searches within the National Death Index, Social Security Administration and New Mexico State Mortality Files. Standardized Mortality Ratios (SMR) and Cox regression models were used in the analyses. Results: Most workers (55%) were hired before 1960, 38% had a college degree, 25% were female, 81% white, 13% Hispanic and 60% had died. Vital status was complete, with only 0.1% lost to follow-up. The mean dose to the lung for the 17, 053 workers monitored for radiation was 28.6 weighted-mGy (maximum 16.8 weighted-Gy) assuming a Dose Weighting Factor of 20 for alpha particle dose to lung. The Excess Relative Risk (ERR) at 100 weighted-mGy was 0.01 (95%CI −0.02, 0.03; n  = 839) for lung cancer. The ERR at 100 mGy was −0.43 (95%CI −1.11, 0.24; n  = 160) for leukemia other than chronic lymphocytic leukemia (CLL), −0.06 (95%CI −0.16, 0.04; n  = 3043) for ischemic heart disease (IHD), and 0.29 (95%CI 0.02, 0.55; n  = 106) for esophageal cancer. Among the 6499 workers with measurable intakes of plutonium, an increase in bone cancer (SMR 2.44; 95%CI 0.98, 5.03; n  = 7) was related to dose. The SMR for berylliosis was significantly high, based on 4 deaths. SMRs for Hispanic workers were significantly high for cancers of the stomach and liver, cirrhosis of the liver, nonmalignant kidney disease and diabetes, but the excesses were not related to radiation dose. Conclusions: There was little evidence that radiation increased the risk of lung cancer or leukemia. Esophageal cancer was associated with radiation, and plutonium intakes were linked to an increase of bone cancer. IHD was not associated with radiation dose. More precise evaluations will await the pooled analysis of workers with similar exposures such as at Rocky Flats, Savannah River and Hanford.